The Influence of Collective Leadership on Pastoral Ministry Effectiveness and Congregation Growth - Ponco Mujiono; Daniel Ari Wibowo (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2023)
Shepherding has been an ongoing task throughout the history of the Church of God on Earth. From the day of Pentecost (Acts 2) until the rapture of the Church (1 Thess. 4: 13-18), the Church of the Lord will continue to exist on Earth, necessitating the shepherding of the church's ministers. This study seeks to assess the extent of the influence of collective leadership on the effectiveness of pastoral Ministry and church growth. In this research, the independent variable is